ответ: x = - 1.
Пошаговое объяснение:
Решим уравнение через дискриминант.
(- x - 4) * (3x + 3) = 0
- 3x² - 3x - 12x - 12 = 0
- 3x² - 15x - 12 = 0
D = b² - 4ac = (- 15)² - 4 * (- 3) * (- 12) = 225 - 144 = 81
x₁ = (- b - √D)/(2a) = (- (- 15) - √81)/(2 * (- 3)) = (15 - 9)/(- 6) = 6/(-6) = - 1
x₂ = (- b + √D)/(2a) = (- (- 15) + √81)/(2 * (-3)) = (15 + 9)/(- 6) = 24/(- 6) = - 4
- 1 > - 4 ⇒ в ответ записываем x = - 1.
Решим уравнение через разложение трёхчлена.
(- x - 4) * (3x + 3) = 0
[ - x - 4 = 0 x₁ = - 4
⇒
[ 3x + 3 = 0 x₂ = - 1
- 1 > - 4 ⇒ в ответ записываем x = - 1.
Б) 1. 72,492:12=6,041 ; 2. 78,156:36=2,171 ; 3. 123,03:15=8,202 ; 4. 6,041+2,171+8,202= 16,414
Е) 1. 9:0,3=30 ; 2.16:0,2=80 ; 3. 30-80= -50; 4. -50 : 0,016= - 3125